Kepemimpinan Perempuan dalam Tim Kerja Gay : Sebuah Perspektif Queer - Rio Putra Pratama (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Women's leadership in work teams or organizations is currently increasing. This shows the impact of the gender mainstreaming movement which is one of the Sustainable Development Goals (SDGs). Apart from that, based on 2018-2021 McKinsey research, the results showed that women's leadership can create an egalitarian climate in work teams and be inclusive of people of diverse genders and sexualities or queer people, including gay people. This paper discusses women's leadership in gay work teams, with a focus on the perspective of gay members in work teams. This research uses a qualitative approach with a case study type. The analysis in this research uses Queer Theory which was coined by Judith Butler. The findings of this research are that women's leadership in gay work teams is compatible because women and gays have the same problems, namely patriarchy and heteronormativity. This causes women to have empathy for gays because they also experience the same problems. Women also have gender-conscious empathy.